Non-invasive High-Frequency Oscillatory Ventilation as Initial Respiratory Support for Preterm Infants With Respiratory Distress Syndrome - Lai, Shu-Hua; Xie, Ying-Ling; Chen, Zhi-Qing; Chen, Rong; Cai, Wen-Hong; Wu, Luo-Cheng; Lin, Yun-Feng; Zheng, Yi-Rong (Frontiers in Pediatrics, 2022)
Objectives: The aim of this study was to investigate the safety and feasibility of nHFOV as initial respiratory support in preterm infants with RDS. Methods: This study retrospectively analyzed the clinical data of 244 premature infants with RDS who were treated in our hospital from January 2016 to January 2019, and according to the different initial respiratory support methods, them were divided into nHFOV group (n=115) and BiPAP group (n=129). Results: The respiratory outcomes showed that the rate of NIV failure at the first 72 hours of life in the nHFOV group was significantly lower than that in BiPAP group. The time of NIV in nHFOV group was significantly shorter than that in BiPAP group. The time of supplemental oxygen in nHFOV group was significantly shorter than that in BiPAP group. The incidence of air leakage syndrome in the nHFOV group was significantly lower than that in the BiPAP group, and the length of hospital stay of the nHFOV group was also significantly shorter than that in the BiPAP group. Though the rate of infants diagnosed with BPD was similar between the two groups, the rate of severe BPD in the nHFOV group was significantly lower than that in the BiPAP group. Conclusion: This study showed that nHFOV as initial respiratory support for preterm infants with RDS was feasible and safe compared to BiPAP. Furthermore, nHFOV can reduce the need for IMV and reduce the incidence of severe BPD and air leak syndrome.